Manganese oxide increases bleaching efficacy and reduces the cytotoxicity of a 10% hydrogen peroxide bleaching gel - de Oliveira Ribeiro, Rafael Antonio [UNESP]; Zuta, Uxua Ortecho [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Anselmi, Caroline [UNESP]; Soares, Diana Gabriela; Briso, André Luiz Fraga [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2022)
Objective: The study aims to assess the effects of a 10% H2O2 bleaching gel with different MnO2 concentrations on the bleaching efficacy (BE), degradation kinetics (DK) of H2O2, and trans-amelodentinal cytotoxicity (TC). Materials and methods: Standardized bovine enamel/dentin disks (n = 96) were placed in artificial pulp chambers, and the bleaching gels were applied for 45 min. Thus, the following groups were established: (G1) no treatment (negative control/NC); (G2) 35% H2O2 (positive control/PC); (G3) 10% H2O2; (G4) 10% H2O2 + 2 mg/mL MnO2; (G5) 10% H2O2 + 6 mg/mL MnO2; and (G6) 10% H2O2 + 10 mg/mL MnO2. After analyzing bleaching efficacy (ΔE00 and ΔWI), the degradation kinetics of H2O2 and trans-amelodentinal cytotoxicity were determined (n = 8, ANOVA/Tukey; p < 0.05). Results: G6 presented BE (ΔE00 and ΔWI) statistically similar to G2, which represented conventional in-office bleaching (p = 0.6795; p > 0.9999). A significant reduction in the diffusion of H2O2 occurred in G3, G4, G5, and G6 compared to G2 (p < 0.0001). The highest DK of H2O2 occurred in G6 (p < 0.0001), which had the lowest TC in comparison with all other bleached groups (p ≤ 0.0186). Conclusion: The addition of 10 mg/mL of MnO2 in a 10% H2O2 bleaching gel potentiates the degradation of this reactive molecule, which increases the BE of the product and decreases TC. Clinical significance: Replacing a 35% H2O2 gel commonly used for conventional in-office dental bleaching by a 10% H2O2 gel containing 10 mg/mL of MnO2 reduces the cytotoxicity of this professional therapy, maintaining its excellent esthetic efficacy.
Keywords: Cell culture; Dental materials; Tooth bleaching; Toxicity